EVALUATION OF HEAVY METALS CONCENTRATIONS OF Verbascum diversifolium AND Alcea calvertii PLANTS - Türkoglu, Tuba; Türkoğlu, Semra (My University, 2023)
Depending on atmospheric and industrial pollution, heavy metals can accumulate in the soil and affect the ecosystem. Plants are important biological controllers of environmental pollution. Elemental analysis in plants is among the alternative effective methods used for ecological research. In this study, the usability of plant species such as Verbascum diversifolium and Alcea calvertii, whose heavy metal content was determined, as biomonitors was investigated. The mineral content measurements of the extracts prepared from the leaves and flowers of the examined plant species were made with an Inductively Coupled Plasma Optical Emission Spectrophotometer (ICP-OES). Heavy metal (Cd, Pb, Cr, As, Zn, Ni) concentrations in plant extracts were determined. In our study, it was determined that the heavy metal tolerance of these two plant species was high. It is thought that it will be important to determine plant species resistant to heavy metals, to clean nature and to prevent human-induced heavy metal pollution from becoming a major problem for all living things in the future.
Keywords: Verbascum diversifolium; Heavy Metal; Alcea calvertii